Implementasi Model PBL Berbasis Gamifikasi Berbantuan Wordwall untuk Meningkatkan Kemampuan Pemecahan Masalah Peserta Didik Kelas VII Pada Materi Zat Dan Perubahannya di SMP Negeri 1 Padang - Putri, Mayang Lisda; Yanto, Febri; Arif, Khairil; Sari, Widia Kemala (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study was motivated by the low problem-solving skills of students due to learning that is still dominated by conventional methods and the lack of interactive media, resulting in students tending to be passive in their learning. This study aims to determine the effect of applying a gamification-based Problem-Based Learning (PBL) model assisted by Wordwall on the problem-solving skills of seventh-grade students at SMP Negeri 1 Padang. This study used a quantitative method with a non-equivalent control group quasi-experimental design. The sample was determined using purposive sampling, with class VII.A as the experimental class and VII.F as the control class. The research instruments consisted of an observation sheet, a student response questionnaire, and a problem-solving ability test in the form of 11 essay questions. Data analysis was conducted through normality tests, homogeneity tests, and t-tests. The results showed that the implementation of learning reached an average of 94% (very good category) and student responses were 88% (positive category). The t-test results showed that Tcount > Ttable (2.05 > 2.00), which means that there was a significant difference between the two classes. Thus, the application of gamification-based PBL assisted by Wordwall had a significant effect on improving students' problem-solving skills